Photosensitizer-free, gold-catalyzed c-c cross-coupling of boronic acids and diazonium salts enabled by visible light - Witzel, Sina; Xie, Jin; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2017)
The first photosensitizer-free visible light-driven, gold-catalyzed C-C cross-couplings of arylboronic acids and aryldiazonium salts are reported. The reactions can be conducted under very mild conditions, using a catalytic amount of tris(4-trifluoromethyl)phosphinegold(I) chloride [(4-CF3-C6H4)3PAuCl] with methanol as the solvent allowing an alternative access to a variety of substituted biaryls in moderate to excellent yields with broad functional group tolerance.
Gesehen am 28.08.2017